Present - "Johnson, Spencer" (London, 2006)
From the author of Who Moved My Cheese comes another book that teaches life lessons through a simple fable. The Present: The Secret To Enjoying Your Work And Life, Now! is an engaging story about a young man?s journey through life and how he learns ways to solve life?s problems through the simple wisdom taught by an old man. When he was a boy, the young man comes across a wise old man who talks to him about something called The Present. The old man tells the boy that The Present is the greatest gift that anyone can receive. The puzzled boy asks the old man what it is, but receives no direct answer. In his teens, the boy sees the old man again. This time, when the boy asks him about The Present, the old man says that he already knows what it is and asks the boy to recollect how involved he was when he was cutting the grass. Still unable to understand, the boy gives it up. The boy is now a young man who has a good job, but he soon runs into a crisis when he is passed over for promotion. He goes to see the old man who advises him to live for a while in isolation, in the mountains. There he finally understands what the old man was trying to tell him all along
Keywords: Psychology